ERYTHROPOIESIS AND HORMONAL FACTORS (ERYTHROPOIETIN, THYROID HORMONES, SEX STEROIDS) - Tatevik Melkumyan (Modern American Journals, 2025)
The article analyzes the influence of hormonal factors on the processes of erythropoiesis. The central regulator is erythropoietin, which ensures the survival and differentiation of erythroid precursors. Thyroid hormones increase the synthesis of erythropoietin and directly stimulate cell proliferation, which explains the development of anemia in hypothyroidism and erythrocytosis in thyrotoxicosis. Sex steroids have a dose-dependent effect: testosterone enhances the production of erythropoietin and bone marrow sensitivity, while estrogens have a modulating and inhibiting effect. The molecular mechanisms of these interactions, their significance for the pathogenesis of anemia and polycythemia, as well as clinical consequences during hormonal therapy are analyzed.
Keywords: Erythropoiesis, erythropoietin, thyroid hormones, testosterone, estrogens, sex steroids, hypoxia, anemia, erythrocytosis, regulation of hematopoiesis.